MANAJEMEN PERPUSTAKAAN BERBASIS LITERASI DIGITAL UNTUK PENINGKATAN PRESTASI PESERTA DIDIK DI SMA NEGERI BERAU - Kusmiati, Tati; Nurlaili, Nurlaili; Akhmad, Akhmad; Warman, Warman; Mulawarman, Widyamitmike G; Azainil, Azainil (JURNAL EDUCATION AND DEVELOPMENT, 2025)
The transformation of traditional libraries into digital ones has become essential for the learning process. On one hand, libraries are required to provide digital resources, while on the other hand, students are expected to be literate. This study employs a qualitative approach using a case study method. The research was conducted at SMA Negeri 1 and SMA Negeri 4 Berau, utilizing data collection techniques such as observation, interviews, and documentation. Data analysis was carried out using the interactive model of Miles and Huberman and Pattern Matching by Robert K. Yin. The findings indicate that digital-based library planning in both schools begins with identifying the need for digital resources. In terms of organization, both schools have a clear management structure. The implementation stage involves various strategic programs in both schools. During the evaluation phase, both schools apply a continuous monitoring and assessment system. The impact of digital libraries has been positive, enhancing students' achievements by supporting their preparation for competitions. Additionally, the pattern-matching results conclude that the library management in both schools aligns with the theoretical framework. In conclusion, the four main aspects of educational management have been effectively implemented in both schools. The implication of this research reinforces the concept of digital literacy, emphasizing the importance of utilizing digital resources critically